2023
DOI: 10.1002/iid3.810
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cell‐derived exosomes improve oxidative stress and pyroptosis in doxorubicin‐induced myocardial injury in vitro by regulating the transcription of GSDMD through the PI3K‐AKT‐Foxo1 pathway

Abstract: Objectives Doxorubicin (DOX) can contribute to severe myocardial injury, and bone marrow stromal cells (BMSC)‐exosomes (Exos) improves acute myocardial infarction. Hence, this research investigated whether BMSC‐Exos alleviated DOX‐induced myocardial injury. Methods BMSC‐derived Exos were isolated and identified, and the optimal concentration of DOX was confirmed. H9C2 cells were treated with DOX and BMSC‐Exos or in combination with the protein kinase B (AKT) inhibitor. Reactive oxygen species (ROS) and JC‐1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Transplantation of BM-MSC-EXOs has been shown to functionally alleviate DIC in mice via suppression of the inflammatory response of cardiomyocytes and inflammation-related cell death [ 31 ]. In vitro study has also revealed that BM-MSC-EXO treatment robustly restrained DOX-induced pyroptosis and oxidative stress of myocardial cells via diminished GSDMD expression by regulating the PI3K-AKT-Foxo1 pathway [ 32 ]. To obtain a large volume of MSC-EXOs for transplantation, BM-MSCs need to be expanded extensively in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of BM-MSC-EXOs has been shown to functionally alleviate DIC in mice via suppression of the inflammatory response of cardiomyocytes and inflammation-related cell death [ 31 ]. In vitro study has also revealed that BM-MSC-EXO treatment robustly restrained DOX-induced pyroptosis and oxidative stress of myocardial cells via diminished GSDMD expression by regulating the PI3K-AKT-Foxo1 pathway [ 32 ]. To obtain a large volume of MSC-EXOs for transplantation, BM-MSCs need to be expanded extensively in vitro.…”
Section: Discussionmentioning
confidence: 99%